The relationship between resilience, perceived organizational support and mental health among nurses - Muhamad Yusof, Ghazali (2018)
The issue of mental health at workplace had recently highlighted after seeing a visible increase in the number of workplace related mental health cases in Malaysia. Nurses are not been excluded to be one of the group of employees who are having mental health issues since their play an important role in the health care system. Therefore, this study was conducted to investigate the possible variables that could better explain the level of mental health among nurses by investigating the relationship between resilience, perceived organization support (POS) and mental health. Affective Event Theory (AET) was used to explain the possible relationship between the variables to support the research framework. A total of 321 of nurses at Hospital Pulau Pinang were participated in this study. Data was collected via self-administered questionnaires and SPSS was used to analyse the data and test hypothesis. Result show that resilience and POS are positively related to mental health. Moreover, the level of mental health among nurses at HPP is at medium level and highly being influence by POS. Finally, the implication for managerial, individual and academic and some recommendation for future research are discussed.